Research progress in endothelial cell injury and repair - Huang, Yongpan; Song, Chong; He, Jianbin; Li, Min (Frontiers in Pharmacology, 2022)
Endothelial cells are important metabolic and endocrine organs and play an important role in regulating vascular function. The occurrence and development of various cardiovascular and cerebrovascular diseases (such as atherosclerosis, hypertension, diabetic vascular complications) are closely related to endothelial dysfunctions. However, the mechanism of vascular endothelial injury is not fully understood. A large number of studies have shown that the mechanism of endothelial injury mainly involves inflammatory response and oxidative stress. Endothelial progenitor cells play an important role in repairing damaged endothelium. A variety of chemical drugs and traditional Chinese medicines exert endothelial protection by reducing inducing factors, inhibiting inflammatory and oxidative stress, and delaying endothelial cell aging.